Utilizing Facebook as a Marketing Medium for Traditional MSMEs: A Case Study of the Sihobuk Peanut Business in Sipoholon District - Sabda Dian Nurani Siahaan; Lenti Susanna Saragih; Dede Ruslan (Economic: Journal Economic and Business, 2025)
Technological developments are currently increasingly prevalent and have merged into various aspects of human life. One aspect that is greatly penetrated and influenced by technological advances is the business and entrepreneurship sector. Currently, the MSME sector is expected to increase not only in terms of quantity, but also in quality through reforming business implementation from conventional to digital-based. Business digitalization can be applied to various business activities, one of which is in the marketing sector. Sihobuk peanuts are a native product originating from North Tapanuli Regency. Sihobuk peanut entrepreneurs in Sipoholon District are experiencing stagnant conditions and low business revenues, allegedly due to the lack of implementation of marketing digitalization. This study aims to conduct and implement marketing digitalization through Facebook social media and measure its impact on business revenue. The study was conducted on five Sihobuk peanut MSMEs using the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) method. The results showed a 20%–30% increase in revenue after implementing Facebook social media marketing for three months. The implementation of marketing digitalization has proven effective in increasing the income of Sihobuk peanut MSMEs and is a practical solution for traditional business actors in the digital era.